1981
DOI: 10.1530/acta.0.0970150
|View full text |Cite
|
Sign up to set email alerts
|

Opiate receptors and anterior pituitary hormone secretion in man. Effect of naloxone infusion

Abstract: The role of endogenous opioid receptors on anterior pituitary hormone secretion was evaluated by the administration of the opioid receptor antagonist naloxone. The infusion of naloxone (8 mg iv followed by 4 mg/h for 3 h) did not alter basal growth hormone (GH), prolactin (Prl) and thyrotrophin (TSH) secretion but produced a significant rise in cortisol and gonadotrophins in normal man. The infusion of the opiate antagonist appeared to increase the rate and amplitude of luteinizing hormone (LH) pulsatility. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 14 publications
2
37
0
1
Order By: Relevance
“…Contradictory data exist about the effects of naloxone on PRL and TSH secretion. Some au thors reported a decrease in TSH levels in normal human volunteers [12], other studies failed to show any effect both in normal [3,28] and hypothyroid subjects [13,28], Nalox one seems to have no effects on PRL secretion too [3,16,28], although a reduction in PRL serum levels has been re ported in human subjects [34] as observed in animals [2,41], The reason of these discrepancies is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory data exist about the effects of naloxone on PRL and TSH secretion. Some au thors reported a decrease in TSH levels in normal human volunteers [12], other studies failed to show any effect both in normal [3,28] and hypothyroid subjects [13,28], Nalox one seems to have no effects on PRL secretion too [3,16,28], although a reduction in PRL serum levels has been re ported in human subjects [34] as observed in animals [2,41], The reason of these discrepancies is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the administration of opiate-receptor antagonists alone significantly amplifies the pulsatile mode of LH release, with attendant increases in the frequency and peak amplitude ofboth immunoactive and biologically active LH pulses (1 1-15). The ability of opiate-receptor antagonists to enhance episodic LH secretion in vivo (11)(12)(13)(14)(15) and to stimulate gonadotropin-releasing hormone (GnRH) secretion from human hypothalamic tissue in vitro (16,17) has suggested that the inhibitory action of endogenous opiates is exerted at the level of the hypothalamic pulse generator for GnRH.…”
Section: Introductionmentioning
confidence: 99%
“…The acute administration of opioid peptides may have no effect (8), may inhibit (9), or may increase (2, 10 -13) basal or TRH-stimulated TSH release. Moreover, several studies have found that naloxone, in doses up to 20 mg, had no effect on basal and stimulated TSH secretion (1,5,14,15), whereas other authors have found a decrease in basal TSH secretion (11, 16) or a blunted TSH response to TRH or exogenous opiates (16, 17) in normal subjects.In a recent study (18), we found a dose-dependent inhibitory action of cortisol on TSH secretion in Addison patients (18). Our results suggested a glucocorticoid-mediated suppression of the pituitary sensitivity to TRH, although a synergistic effect at the hypothalamic level could not be excluded.…”
mentioning
confidence: 99%
“…Although exogenous opioid peptides consistently increase the secretion of PRL (8,10,12), conflicting results concerning the effects of naloxone on PRL release have been published. Most studies have reported no effect of naloxone on basal (5,11,14,15,20), stress-, or exercise-induced (1,11,21,22) and TRH-induced (14, 17) levels of PRL. Some studies have found a naloxone-induced inhibition of PRL release (23).…”
mentioning
confidence: 99%